Território da cidadania do Cariri: os programas de fortalecimento da Agricultura Familiar - Costa Junior, Juscelino Martins (2019)
The attention of the State to the Brazilian countryside was for a long time focused only on the medium and large producer. In the mid-1990s family farming was considered in some state actions. In this sense, programs and public policies were implemented. Thus, the objective of this work was to verify the role of the State, through its actions and programs of public policies, in the strengthening of rural settlements in the Citizenship Territory of Cariri Ceará. As a methodology was carried out a qualitative study, with the application of questionnaires and semi-structured interviews, as well as participatory observation methods. In 2008, the Territory of Citizenship program was created and in 2009 the program began in Cariri, the largest in Ceará, with 29 municipalities. It was found that few settlers were able to access programs such as the PNAE and the PAA. Low access to the Programs was linked to local environmental characteristics and lack of technical assistance and rural extension services. The NEDET's aim is to support territorial colleges, to disseminate methods and technologies geared to the social management of territorial politics, but it has not been able to attend and not to insert the federal settlements in its plan of action. The State, with all its policies, has the potential to promote development in settlements and for all family agriculture in Cariri, but it is necessary to work more steadily with a network of actors who favor agriculture.